Optimizing Interior Design for the Girls' Dormintory at an Islamic High School in West Java - Cardiah, Tita; Firmansyah, Rangga; Kurniawan, Filsa Andiani (Perhimpunan Intelektual Muslim Indonesia, 2025)
Dormitories for girls at the secondary education level require facilities that are suitable for the needs of girls aged between 12 and 18 years. This research aims to determine the optimal spatial layout for girls' dormitories, based on the space requirements for both main activities and supporting activities, using a sample of five boarding schools in West Java. The research employs a qualitative descriptive method that commences with data collection through surveys, observations, and a review of relevant literature pertaining to dormitories. This research not only begins by analyzing the existing spaces but also delves into factors influencing the presence of these spaces, specifically examining the availability of dormitory, and supporting room facilities through the assessment of suitability using a survey checklist of various variables. The results indicate that different space optimization patterns were observed in the five boarding schools, which depended on the management concept of each dormitory. These patterns were adjusted to the existing conditions of the dormitory, considering the adaptation and utilization of available spaces. In general, all dormitories have met the standards and space optimization patterns according to the criteria set by each dormitory manager. Consequently, further research is warranted, particularly in relation to the management concept and the spatial arrangement based on the dormitory's brand identity.